The trade-off between child quantity and child quality: An application of the Kremer-Chen model to households in rural Terengganu, Malaysia - Abdul Razak, Nor Azam (Canadian Center of Science and Education, 2011)
The idea of the trade-off between child quantity and child quality has long been documented in economics. In the past, this trade-off has been attributed to the rising marginal cost of child quantity and quality. In recent years, this trade-off has been attributed to a declining direct cost of childrearing and an escalating opportunity cost of childrearing induced by rising household income. Exploiting a micro data set from rural Terengganu, we revisit the idea based on this new postulate.Our goal is to investigate whether a rise in household income has a positive impact on child quality and a negative impact on child quantity. In a series of empirical exercises, we find that household income has a positive impact on both child quantity and child quality.We take these findings as evidence that there is no trade-off between child quantity and child quality among rural households in Terengganu, Malaysia.